The occurrence of Scandinavian Hieracium oistophyllum (Asteraceae) in Central Europe confirmed by morphological, cytogenetic and molecular evidence - Grabowska-Joachimiak, Aleksandra; Góralski, Grzegorz; Kwolek, Dagmara; Szeląg, Zbigniew (Phytotaxa, 2025)
Hieracium oistophyllum is an apomictic species widely distributed in northern Europe, primarily in Sweden, from where it was described. Its isolated, southernmost locality in Central Europe was rediscovered in Poland after a century. Morphological, cytogenetic, molecular and phylogenetic analyses revealed no substantial differences between plants from Poland and Sweden, and confirmed that the Polish plants belong to H. oistophyllum. The species is illustrated with photographs of a herbarium specimen and of live cultivated plants.